The Effect of university news production practices in large sports events - a study of Zhejiang Gongshang University's coverage of the Hangzhou Asian Games from user/producer perspective - Guanghe, Ge; Shazleen Mohamed,; Muhammad Nurhafiz Hassim,; Tao, Huang; Zekai, Qiu; Yifan, Xu (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Hangzhou Asian Games, a key international sports event in 2023, provides China with an opportunity to showcase its global standing, following the Beijing Olympic Games and Shanghai World Expo. Zhejiang Gongshang University's Culture and Sports Centre serves as the handball competition venue, with about 1,200 teachers and volunteers engaged across various Asian Games sites. Despite this, the university's media impact falls short compared to peers in Hangzhou with Asian Games venues. This research explores the news production practices of universities during large-scale international sports events, focusing on improving Zhejiang Gongshang University's media coverage and influence. Utilizing in-depth interviews and The Uses and Gratifications theory, the study analyzes news production related to the Asian Games on the university's official website, social media, and newspapers. Interviews include both producers and audiences of this news. Findings indicate a disconnect between media reports and the diverse needs of media users, with news production primarily driven by informational and promotional objectives. Recommendations include diversifying themes and forms of media coverage, enhancing creativity and interactivity, adopting a proactive and strategic approach to media communication, and leveraging new media platforms for more engaging content.